A candle in the wind. Issue 4 (4th July 2022) - Dent, David; Boincean, Boris; Dmytruk, Yuriy; Bai, Zhanguo
ABSTRACT: Soil is the biggest brake on global heating. It holds more carbon than the atmosphere and all standing vegetation together but farmers have been burning off soil organic matter for 12000 years: they are responsible for one-third of greenhouse gas emissions. The best thing they could do for the planet is to put it back again, and the best place to start is the best soil in the world – the Black Earth of the steppes, prairies and pampas. Half of its organic matter has been pumped into the air and 35 years of satellite measurements reveal a significant loss of primary productivity across the steppes. Conservation Agriculture can haul back the carbon deficit, increase yields and save 60–70% on fuel, fertiliser and labour; the green biomass can support livestock and/or generate biogas. Ukraine and Moldova were set to adopt this system and phase out their coal-fired power stations when the Russian army invaded Ukraine. The best soil in the world is now being put to other uses; we face a global food crisis; and the world's decision makers have yet another excuse to defer serious efforts to mitigate climate change.